Pediatric septic arthritis of the hip: the benefit of hip arthroscopy by extracapsular (outside-in) approach. Issue 2 (28th February 2020) - Jan, Nicolas; Pietrzak, Julien; Baudoux, Matthieu; Kaba, Arnaud
Background: Pediatric septic arthritis of the hip is a surgical emergency. Facing a hip flexum and fever, surgeons can use comparative ultrasound to confirm the diagnosis and to establish the surgical indication. While needle aspiration-irrigation is a simple and quick method, it gives rise to a high rate of recurrence. The purpose of our study was to demonstrate that hip arthroscopy by extracapsular approach is an effective and accessible alternative applicable in emergency situations. Methods: This is a report of 2 cases (7 years-135 cm; 13 years-143 cm) of needle aspiration-irrigation failure subsequently treated by hip arthroscopy. The X-ray and arthroscopy-assisted extracapsular technique was performed on a conventional orthopedic table, using a 30 degree arthroscope and a 3.5mm diameter motorized knife. Minimally invasive anterior longitudinal capsulotomy was performed by 2 anterolateral approaches via the proximal and distal tensor Fasciae Latae muscle, without dedicated instrumentation, followed by sampling, irrigation, removal of false membranes, synovial biopsies, partial synovectomy, cartilage assessment of the central then peripheral compartment and placement of a drainage. Results: In both cases, effusion completely disappeared and the inflammatory process gradually normalized with antibiotic therapy without any repeat procedure or complications related to the approach. Weight bearing was resumed in 3 weeks. Postoperatively, in 6 months and 15 months respectively, after resumption of sports activities hip examination was painless and no damage was noted on x-rays in either case. Conclusion: In our experience, hip arthroscopy by extracapsular approach can effectively address cases of failed needle aspiration-irrigation in pediatric septic arthritis of the hip. It could be provided as first-line emergency treatment in the event of purulent septic arthritis or late management, as a replacement for arthrotomy.